Part-time and temporary workers in Russia: winners or losers? - Tatiana Karabchuk (Journal for Labour Market Research, 2012)
This paper examines wage differentials between permanent/non-permanent and full-time/part-time employees. The analysis is based on the representative Household Survey of Welfare dataset, collected by Rosstat and the World Bank in 2003. The results show that non-permanent workers suffer a loss in wages while part-timers earn more per hour than full-timers, but the wage gap diminishes substantially when controlled for observed and non-observed characteristics. It seems that the theory of segmented labor markets is quite appropriate for explaining these differences in the Russian labor market.
Keywords: J71; M51; M53; Z13; 330; Lohnunterschied; Teilzeitarbeitnehmer; Vollzeitarbeit; Teilzeitarbeit; befristeter Arbeitsvertrag; unbefristeter Arbeitsvertrag; Arbeitsmarktsegmentation; Zeitarbeitnehmer; Lohnhöhe; Russland